1992
DOI: 10.1016/s0006-3495(92)81882-9
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular protein interactions in solutions of calf lens alpha-crystallin. Results from 1/T1 nuclear magnetic relaxation dispersion profiles

Abstract: From analyses of the magnetic field dependence of 1/T1 (NMRD profiles) of water protons in solutions of calf lens alpha-crystallin at several concentrations, we find two regimes of solute behavior in both cortical and nuclear preparations. Below approximately 15% vol/vol protein concentration, the solute molecules appear as compact globular proteins of approximately 1,350 (cortical) and approximately 1,700 (nuclear) kD. At higher concentrations, the effective solute particle size increases, reversibly, as evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…We can conclude that there is a temperature-induced aggregation or temporal associations but we cannot quantify them. Recently, Koenig et al found that 7-crystallin fractions aggregate as the temperature decreases (Koenig et a]., 1990(Koenig et a]., , 1992. They claim that the phase transition observed in y-crystallin solutions is driven by the formation of these protein aggregates.…”
Section: Second Virial Coefficient Results a Debye Plot [A Plot Of Rmentioning
confidence: 99%
“…We can conclude that there is a temperature-induced aggregation or temporal associations but we cannot quantify them. Recently, Koenig et al found that 7-crystallin fractions aggregate as the temperature decreases (Koenig et a]., 1990(Koenig et a]., , 1992. They claim that the phase transition observed in y-crystallin solutions is driven by the formation of these protein aggregates.…”
Section: Second Virial Coefficient Results a Debye Plot [A Plot Of Rmentioning
confidence: 99%
“…The eye lens protein ␣-crystallin, which has a dynamic oligomeric structure (44,45), has also been isolated as distinct populations in the 600 -900-kDa, 900-kDa-4-MDa, and greater than 10-MDa ranges (46). However, because concentration, pH, ionic strength, and temperature of isolation have all been reported to affect the oligomeric state of ␣-crystallins (47,48) and because IbpA may modulate the quaternary structure of IbpB, it is not clear whether large IbpB oligomers also exist in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…YO solids. ;l In contrast to solutions of mobile protein, the functional form of the dispersions ( 5 2 0 MHz) of 1/T, of immobile protein and tissue (there are few data for 1/T,) is different in several characteristic ways (29): both the temperature dependence and the change upon deuteration of solvent are much reduced; the T,/T, ratio is much enhanced at higher fields; and 14N peaks generally become prominent. These distinctions arise from an increase in the importance of magnetization transfer across the protein-water interface upon immobilization, which then is the major determinant of the observed NMRD profiles.…”
Section: Discussionmentioning
confidence: 99%